Semantic, technical, e-government information systems interoperability and the moderating effect of IT capability among ministries in Jordan - Sulehat, Naser Ahmad (Serials Publications, 2017)
In the past two decades the interoperability of Information Systems counted from the main key feature of successful e-Government projects. While information systems and technologies are being developed and enhanced, many discussions on their success have been accomplished by scholars and researchers. Moreover, they found that achieving of IS interoperability between different institutions is a complex task and influenced by different aspects. As a part of these aspects the semantic and technical factors considered from the main issues related to interoperability. This study investigates the semantic and technical factors that affect the level of interoperability with focusing on interoperability of IS as a key concept to achieve the successful implementation of interoperability in the public sector. In order to explore the variables of the study and its relations, a variety of published literatures on the scope of the study was critically reviewed. Furthermore, data was collected using the survey by distributing 355 questionnaires to IT staff in 25 Jordanian ministries. 231 usable forms were returned. The data was analyzed using the Partial least squares-structural equation modeling technique. The findings showed that the semantic factor and technical factor positively affect the e-GISI. On the contrary, there was no moderate effect of IT capability in the relationship between both semantic and technical factors and the e-GISI. The semantic and technical factors are good for promoting e-GISI, which means that government entities must promote STD as a semantic factor and SAP as technical factor. On contrary, there was no moderating effect of IT capability between semantic and technical factors and the e-GISI among the Jordanian ministries.